ANALISIS FAKTOR-FAKTOR PENYEBAB RENDAHNYA MINAT MEMBACA SISWA PADA MATERI “CINTA INDONESIAKU” DI KELAS V SDN 125 PALEMBANG - Putri Widya Wati; Liza Murniviyanty; David Budi Irawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the factors causing low students' reading interest in the material Love My Indonesia in grade V SDN 125 Palembang. The method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that low reading interest is caused by two main factors, namely internal and external factors. Internal factors include low reading comprehension skills and reading habits that are only done when there is an assignment from the teacher without any encouragement to read independently. Meanwhile, external factors include the school environment, literacy facilities such as libraries including low intensity of borrowing books and wall magazines, and the role of parents. Based on these findings, it can be concluded that increasing reading interest requires synergy between schools and families through the provision of adequate facilities, interesting literacy programs, and early reading habits